2016
DOI: 10.1002/fuce.201500076
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Analysis of a System Based on W and Ni Combined with CeO2 as Potential Sulfur‐tolerant SOFC Anode

Abstract: A formulation of tungsten and nickel combined with CeO 2 (WNi-Ce) was prepared and evaluated as sulfur-tolerant anode for SOFC at intermediate temperature. Structural and morphological changes that take place in the system upon interactions with hydrogen sulfide were analyzed. The electrochemical performance was tested in a single cell, WNi-Ce/ LDC/LSGM/LSFC, varying H 2 S concentration (0-500 ppm) at 750°C using I-V curves, impedance spectroscopy and load demands. The highest cell performance was reached in H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…As can be seen, the cell with the FeNi 3 /RP‐LSFN‐infiltrated SDC anode had slightly higher electrolyte resistances in 1000 ppm H 2 S‐H 2 fuel (0.453 Ω cm 2 ) as compared with that of H 2 fuel (0.452 Ω cm 2 ). In addition, the electrode polarization resistance obtained in the H 2 and 1000 ppm H 2 S‐H 2 are 0.023 and 0.026 Ω cm 2 , the decrease in cell performance is mainly related to an increase in the electrode polarization resistance, this can be due to the result of surface adsorption of sulfur on active sites and/or formation of sulfides, suggesting the good sulfur tolerance of the FeNi 3 /RP‐LSFN‐infiltrated SDC anode. The above results suggested that the FeNi 3 /RP‐LSFN‐infiltrated SDC anode had excellent sulfur tolerance for operation with H 2 S‐containing fuel, which can be assigned to the high O 2− conductivity of Ruddlesden‐Popper type perovskite that can eliminate the deposited sulfur on the Ni surface …”
Section: Resultsmentioning
confidence: 99%
“…As can be seen, the cell with the FeNi 3 /RP‐LSFN‐infiltrated SDC anode had slightly higher electrolyte resistances in 1000 ppm H 2 S‐H 2 fuel (0.453 Ω cm 2 ) as compared with that of H 2 fuel (0.452 Ω cm 2 ). In addition, the electrode polarization resistance obtained in the H 2 and 1000 ppm H 2 S‐H 2 are 0.023 and 0.026 Ω cm 2 , the decrease in cell performance is mainly related to an increase in the electrode polarization resistance, this can be due to the result of surface adsorption of sulfur on active sites and/or formation of sulfides, suggesting the good sulfur tolerance of the FeNi 3 /RP‐LSFN‐infiltrated SDC anode. The above results suggested that the FeNi 3 /RP‐LSFN‐infiltrated SDC anode had excellent sulfur tolerance for operation with H 2 S‐containing fuel, which can be assigned to the high O 2− conductivity of Ruddlesden‐Popper type perovskite that can eliminate the deposited sulfur on the Ni surface …”
Section: Resultsmentioning
confidence: 99%
“…The main characterization of WNi-Ce, synthesized by Performance of Ceria-electrolyte Solid Oxide Fuel Cell Using Simulated Biogas Mixtures as Fuel coprecipitation within inverse microemulsion, has been previously reported [14,15]. After calcination in air this material is mainly constitutes by the fluorite phase of CeO 2 together with a second one of NiWO 4 .…”
Section: Anode Materials Characterizationmentioning
confidence: 99%
“…On the other hand, WS 2 has been studied as anode material in H 2 S oxidation fuel cells to improve performance [12,13] and the results revealed that it was stable and active during the testing time of 36 h. Then, an interesting alternative to favor the direct utilization of biogas as fuel in SOFCs could be a bimetallic formulation of nickel and tungsten combined with CeO 2 (WNi-Ce) as anode material. In previous papers, we have reported that this compound (WNi-Ce) exhibits a high sulphur tolerance and could be operated at sulphur levels up to 500ppm without degradation in the cell performance [14], as well as a low performance in biogas with 10ppm H 2 S at 850°C using LSGM as electrolyte [15]. Furthermore, several benefits in terms of cell lifetime and thermo-mechanical resistance are achieved by decreasing the operating temperature to 500-750 °C, leading to Intermediate Temperature SOFCs (IT-SOFCs) [16].…”
Section: Introductionmentioning
confidence: 99%
“…It is considered that Ni/YSZ degrades at an accelerated rate in practical fuel environments. In the search for a stable anode material, various strategies have been proposed, including replacing nickel with another metal such as Copper [19,20], Tungsten [21], and Molybdenum. Additionally, the ceramic phase can be substituted with a Mixed Ionic Electronic Conductor (MIEC), such as ceria or other perovskite materials, to improve the performance of the fuel cell [22].…”
Section: Introductionmentioning
confidence: 99%
“…Reduced ceria is expected to be a better adsorbent for H 2 S than the corresponding oxidized form. While the exact kinetics of the chemisorption remain unknown, even elemental sulfur can form during the desorption step [10,21]. From the catalysis literature, we know that ceria is an excellent catalyst for the oxidation of HCl at temperatures ranging from 350 to 450 ℃ in the presence of an excess amount of oxygen [28].…”
Section: Introductionmentioning
confidence: 99%